Modeling of a solar photovoltaic converter in the specialized Matlab software - Zibalov, D. (Energy and Automation, 2025)
The developed model of a solar photovoltaic converter (SPC) based on a single-diode model, taking into account shunt and series resistances, photocurrent, and diode reverse current, is used for analyzing the electrical characteristics of the SPC and determining the maximum power point (MPPT) under varying illumination and temperature conditions. The model is implemented in the MATLAB environment, providing the capability for straightforward simulation of physical processes in photovoltaic cells. The proposed method allows obtaining accurate current-voltage characteristics, taking into account the temperature and illumination of the SFС. The implementation of the model in MATLAB simplifies and accelerates its use for the study of MPPT algorithms and autonomous photovoltaic systems. The built-in MATLAB algorithm is used to calculate the current, since the equation of one diode is transcendental and nonlinear with respect to current, and direct analytical methods do not solve it. The results obtained will increase the speed of obtaining current-voltage characteristics of the SFС and determining the maximum power point without the need for lengthy experimental measurements. This will accelerate the development and optimization of autonomous and integrated photovoltaic systems, evaluate the efficiency of the SFP under various conditions, and also simplify testing and verification of MPPT algorithms in the MATLAB environment. Key words: solar photovoltaic converter, resistance, current-voltage characteristic, voltage source, mathematical model